2011
DOI: 10.4236/jep.2011.27114
|View full text |Cite
|
Sign up to set email alerts
|

The New Methods for Purifying the Industrial Effluents by Submerged Biofilm Reactors

Abstract: Life on the earth is dependent on dynamic interactions between its physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Methods such as hydrolysis of the CW, yeast adaptation and pressure selection are empoyed to overcome this problem. A recent research [115], found that SMFBR is also a suitable method to face this problem and to treat CW as well as all dairy effluents. In order to clarify some of the above discussed aspects, the COD removal efficiency rate versus HRT (day) and OLR [g COD/(L day)] are presented in Figure 3.…”
Section: Conventional (Single Phase) Anaerobic Treatment Of Cheese Wheymentioning
confidence: 99%
“…Methods such as hydrolysis of the CW, yeast adaptation and pressure selection are empoyed to overcome this problem. A recent research [115], found that SMFBR is also a suitable method to face this problem and to treat CW as well as all dairy effluents. In order to clarify some of the above discussed aspects, the COD removal efficiency rate versus HRT (day) and OLR [g COD/(L day)] are presented in Figure 3.…”
Section: Conventional (Single Phase) Anaerobic Treatment Of Cheese Wheymentioning
confidence: 99%
“…For example, in the resonance region, if the exciting energy of the neutron absorber nucleus (BE+KE) equals one of the exciting levels (ΔE), then, an absorption occurs, and the absorbed neutron (in the nucleus) may cause the capturing and (n,γ) reaction. Also, after the formation of the compound nucleus, the nucleus may release a neutron such that its energy is very lower than the initial neutron energy, and the remainder nucleus returns to a stable level through emitting  radiation that is an indicator of an inelastic reaction [15]. When ΔE>BE+KE, no absorption occurs, and the neutron gives a small amount of its energy to the target nucleus, and it will be scattered with a new angle based on the reaction (n,n').…”
Section: Neutron and Its Interactions With Materialsmentioning
confidence: 99%
“…Biofilms are surface-associated bacterial communities encapsulated by a self-produced extracellular matrix, and a predominant growth mode of bacteria in nature [3][4][5]. Biofilms are involved in aspects many of our lives, such as medical care [6], effluents purifying [7], biofuel cells [8]. When growing with limited space and nutrient resources, biofilms exhibit cooperative or competitive behaviors to respond effectively to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%